Isotope effect physics, turbulence and long-range correlation studies in the TJ-II stellarator. (15th September 2015) - Liu, B.; Pedrosa, M.A.; van Milligen, B.Ph.; Hidalgo, C.; Silva, C.; Tabarés, F.L.; Zurro, B.; McCarthy, K.J.; Cappa, A.; Liniers, M.
Abstract: The impact of isotope mass on the radial correlation length ( ) and long-range correlation (LRC) of plasma turbulence has been investigated in electron cyclotron resonance heated (ECRH) low-density deuterium-hydrogen plasmas in the TJ-II stellarator. We find that the increases with the deuterium/hydrogen ( D / H ) ratio. However, the amplitude of LRC decreases slightly with the D / H ratio, in contrast to previous results in tokamak plasmas Xu et al (2013 Phys. Rev. Lett .110 265005). These findings show the impact of the isotope effect on both the largest scales (LRC determined by the size of the device) and the characteristic radial scale of turbulent structures.